Quality Characteristics, Cold Chain System, Yield and Productivity of Frozen Tuna (Thunnus albacares) Steak Processing - Sayuti, Mohammad; Rafiani, Evi; Salampessy, Randi B.S. (Politeknik Kelautan dan Perikanan Karawang, 2023)
One of the prospective products that can be developed from tuna is frozen tuna. One processing technique to preserve tuna fish is generally through freezing. F frozen tuna steak is one of the many processed tuna products produced through freezing. The aim of the research is to analyze quality characteristics, application of the cold chain system, calculation of yield and productivity in the processing of frozen tuna steaks at PT. Wahyu Pradana Binamulia. The research method uses a qualitative descriptive method with research stages including process flow observation, organoleptic quality measurements, microbiology (ALT, E. coli, Salmonella), chemistry (histamine), yield calculations, productivity calculations. The data collection method was by directly following processing activities and interviews for the frozen tuna steak processing process, while other data was carried out by testing. The results of the research obtained the processing flow of frozen tuna steak at PT. Wahyu Pradana Binamulia has 23 stages. The organoleptic test results for raw materials have a value of 8 and the final product has a value of 9. The raw material test results for ALT are 6.2 x 103 col/g, Coliform <3 MPN/g, E. coli <3 MPN/g and Salmonella with negative results. The final product test results were ALT 5.5 x 103 col/g, Coliform <3 MPN/g, E. coli <3 MPN/g, and Salmonella with negative results. The histamine test results obtained were 6.9 ppm in the raw material and 7.4 ppm in the final product. Observation results of raw material and product temperatures ≤4.4°C, room temperature ≤20°C and air temperature ≤4.4°C. The yield at the weeding stage was 78.37%, loin formation was 69.40%, dark meat separation and skin removal was 60.77%, trimming was 45.11%, steak formation was 40.48%, retauching was 39. 02%. Employee productivity results at the weeding stage had an average value of 1,214.23 kg/hour/org, for the trimming stage 530.12 kg/hour/org, for the steak formation stage 599.66 kg/hour/org. It can be concluded. The research conclusions show that the quality of raw materials and frozen tuna steak products has met the established SNI standards.